2013
DOI: 10.1007/s00774-013-0474-5
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between calcaneus stiffness index calculated by QUS and total body BMD assessed by DXA in Chinese children and adolescents

Abstract: Few studies have shown comparison data between calcaneus stiffness index (SI) calculated by quantitative ultrasound (QUS) and bone mineral density (BMD) measured by dual-energy X-ray absorptiometry (DXA) in the Chinese population. This study was aimed to examine the correlations between calcaneus SI calculated by QUS and total body BMD and bone mineral content (BMC) measured by DXA in Chinese children and adolescents. We measured the total body BMD and BMC using Lunar Prodigy (GE Healthcare), and speed of soun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 46 publications
1
39
1
Order By: Relevance
“…The OSI measured by QUS in our study reportedly correlates with the dual X-ray absorptiometry measurement of Bone Mineral Density (BMD) used to diagnose osteoporosis 33) . It is also reportedly eff ective in assessing the risk of bone fractures in the proximity of the femur in post-menopausal women 34,35) and predicting the risk of fractures in various ethnicities 36,37) . Table 3 shows the relationship between the predicted infl uencing factors and the OSI.…”
Section: Discussionmentioning
confidence: 99%
“…The OSI measured by QUS in our study reportedly correlates with the dual X-ray absorptiometry measurement of Bone Mineral Density (BMD) used to diagnose osteoporosis 33) . It is also reportedly eff ective in assessing the risk of bone fractures in the proximity of the femur in post-menopausal women 34,35) and predicting the risk of fractures in various ethnicities 36,37) . Table 3 shows the relationship between the predicted infl uencing factors and the OSI.…”
Section: Discussionmentioning
confidence: 99%
“…Also, QUS bone outcomes were significantly associated with risk of fractures in older women to a similar extent to DXA (15). Previous studies in children and adolescents indicated significantly positive correlations between DXA and QUS measurements at different skeletal sites (4,18,43). This wide variability might be due to the use of different skeletal sites of measurement because some researchers use the radial site (4), whereas others use the calcaneal site (18,43) as QUS parameters.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies in children and adolescents indicated significantly positive correlations between DXA and QUS measurements at different skeletal sites (4,18,43). This wide variability might be due to the use of different skeletal sites of measurement because some researchers use the radial site (4), whereas others use the calcaneal site (18,43) as QUS parameters. In accordance with these previous studies, our data show a wide variability of correlations (r = .15-.58), depending on the region and the QUS parameter assessed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations